2015
DOI: 10.1515/secm-2013-0326
|View full text |Cite
|
Sign up to set email alerts
|

Novel form-flexible handling and joining tool for automated preforming

Abstract: The production rates of carbon fiber reinforced plastic (CFRP) parts are rising constantly which in turn drives research to bring a higher level of automation to the manufacturing processes of CFRP. Resin transfer molding (RTM), which is seen as a production method for high volumes, has been accelerated to a high degree. However, complex net-shape preforms are necessary for this process, which are widely manually manufactured. To face these challenges a new concept for the manufacturing of carbon fiber preform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…32 The thickness of the fabric is t = 0.75 mm (uncompressed), the density of E-Glass is approx. ρ GF = 2.6 g/cm 3 . Since the density of air ρ Air is much lower than the density of E-glass and can therefore be neglected, equation (1) results in a porosity of the fabric of f = 0.68 (uncompressed), which means that the fabric consists of approx.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 The thickness of the fabric is t = 0.75 mm (uncompressed), the density of E-Glass is approx. ρ GF = 2.6 g/cm 3 . Since the density of air ρ Air is much lower than the density of E-glass and can therefore be neglected, equation (1) results in a porosity of the fabric of f = 0.68 (uncompressed), which means that the fabric consists of approx.…”
Section: Methodsmentioning
confidence: 99%
“…An important part of the measurements is the determination of the air permeability of the stacked plies, the pressure difference and the resulting volume flow rate _ V as a function of the number of plies. The air permeability R is determined in analogy to standard ISO 9237 34 by using equation (3), where A represents the area. The permeability R corresponds to the average flow velocity of the air through the stacked plies.…”
Section: Pressure Measuring and Volume Flow Rate Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Previous research has shown that this combination of gripping principles can achieve a high adaptability for gripping mechanisms and therefore a capability for handling large varieties of objects [20][21][22]. This previous research also examined influences of the airflow rate and vacuum on the state of the granulate material, with a certain solidity of the granulate being reached for the best vacuum seal and thus the highest vacuum.…”
Section: Previous Workmentioning
confidence: 99%
“…Subsequently [ 2 , 95 , 96 ], these technologies were improved and modified in order to achieve the required parameters of preforming process and preforms characteristics, while the binder systems were also adjusted to them in order to obtain the best properties for both the preform, including curved, and the finished product. In a comparative study of various commercial DFP tapes, it was found that thermoplastic binders are also suitable for producing bindered tapes with the desired properties, from which preforms with the required fiber volume fraction can be made [ 97 ].…”
Section: Automatic Preform Layout Using Bindersmentioning
confidence: 99%